Effects of Dietary Protein Levels on Fecal Amino Acids Excretion and Apparent Digestibility, and Fecal and Ileal Microbial Amino Acids Composition in Weaned Piglets - Yang, Zhenguo; Deng, Huan; He, Tianle; Sun, Zhihong; Gifty, Ziema Bumbie; Hu, Ping; Rao, Zebing; Tang, Zhiru (Frontiers in Nutrition, 2021)
Background and Aims: The purpose of this study was to determine the effects of low protein diets with the same Lys, Met + Cys, Thr, and Trp levels as in high protein diets on the fecal amino acid excretion and apparent digestibility, and ileal and fecal microbial amino acids composition in weaned piglets. Methods: Fifty-four 21-day-old Duroc × Landrace × Yorkshire weaned piglets were randomly divided into three groups and fed with corn-soybean meal basal diets, in which the crude protein (CP) content was 20% (H-CP), 17% (M-CP), and 14% (L-CP), respectively. The experiment included a 7-day adaptation period and a 45-day trial period. Six piglets in each group were randomly slaughtered on days 10, 25, and 45 of the trial period, and the intestinal contents, intestinal mucosa, and feces were collected. Results: The results showed that the interaction between feeding time and dietary CP levels was reflected in the apparent digestibility of dietary CP and amino acid (AA) (p < 0.01). With the increase of age, the apparent digestibility of CP and AA were increased (p < 0.01). With the increase of CP levels, the excretion of nitrogen (N) was decreased (p < 0.01), whereas the flow of microbial AA in the ileum and feces were increased (p < 0.01). The interaction between feeding time and dietary CP levels was also reflected in the composition of AA in the ileum and stool of piglets (p < 0.01). The proportion of His, Lyr, Met, Cys, and Ser was lower than the average, whereas the proportion of Phe, Leu, Pro, Ala, Glu, and Asp was higher than the average. With the increase of age, the AA content of microorganisms increased (p < 0.01). Conclusion: All in all, this work revealed the changes of N, CP, and AA excretion and digestibility of feces and microorganisms of piglets under the combined action of different dietary protein levels and different feeding times, and also the changes of AA composition of intestinal microorganisms and AA composition of microorganisms.